The development and concept of an Agricultural Law System - Budzinowski, Roman (Przegląd Prawa Rolnego, 2020)
The aim of the considerations is to show that it is not only desirable (as well as necessary and useful) but also possible to develop an Agricultural Law System, and to propose a discussion on its concept. In the conclusions, the author states that it is now the right time to come back to the idea of Andrzej Stelmachowski, dating back more than thirty-five years, and develop an "Agricultural Law System." There are many reasons for doing so, and they are presented to in the article. The development of such a system is feasible taking into account both, the objective and the subjective conditions. There is no doubt that the realisation of such a serious work will not be easy, but agricultural lawyers have a great deal of experience in working together on various scientific projects, and may also benefit from foreign studies and solutions that can be used as a model. If work on the system started now, the finished material could be ready for submission to publishers at the turn of 2022/2023.